2018
DOI: 10.1155/2018/6178159
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Mannose-Binding Lectin Serum Level in Tubotympanic Chronic Suppurative Otitis Media

Abstract: Background Chronic suppurative otitis media (CSOM) is a common public health problem worldwide and a major cause of hearing impairment especially in developing countries. The role of Mannose-Binding Lectin (MBL), a component of innate immunity, in CSOM has not been studied. The aim of the study was to examine whether MBL deficiency was more frequently present in cases group of tubotympanic CSOM patients rather than healthy subjects. Material and Methods This was an analytic observational study. Subjects were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…It has been suggested that MBL deficiency plays an important role in host defence, especially during the vulnerable period of infancy between 6 and 17 months of age, when maternal antibodies wane and the adaptive immune system is still developing 18 . These factors make children susceptible to infection by specific pathogens such as S. pneumoniae -one of the most important pathogens causing respiratory tract infections 20 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that MBL deficiency plays an important role in host defence, especially during the vulnerable period of infancy between 6 and 17 months of age, when maternal antibodies wane and the adaptive immune system is still developing 18 . These factors make children susceptible to infection by specific pathogens such as S. pneumoniae -one of the most important pathogens causing respiratory tract infections 20 .…”
Section: Discussionmentioning
confidence: 99%